A Duty Cycle Control Technique for Elimination of Line Current Harmonics in Single-Stage DCM Boost PFC Circuit - H. S., Athab (2008)
for low conversion ratios boost rectifier has a power factor less than unity when operated in discontinuous conduction mode and constant duty cycle. This paper proposes a simple duty cycle modulation technique to reduce the line harmonics and improve the power factor of the boost rectifier, even for low conversion ratios. A periodic-voltage signal is used to vary the duty cycle of the boost switch within a line cycle so that the line current THD is reduced. The proposed technique eliminates the additional harmonic generator, phase detecting and phase-locking circuits. instead, the bridge rectifier's output voltage of the boost converter is used to modulate the duty cycle of the boost switch. As a result, the modulating signal is naturally synchronized with line current. Furthermore, to obtain nearly constant harmonic content over a wide range of load variation, the duty cycle modulation is obtained as the product of the voltage control loop output and the modulation function instead of summing them. Moreover, the rectifier shows a good transient performance where the converter's output voltage overshoots during input voltage/load transients is reduced. Simulation and experimental results are presented to confirm the validity of the method.